Effectiveness of internal marketing at NGO and its influence on Volunteers´ performance and loyalty - Dobersztyn, Aleksandra Maria (2022)
The purpose of this study is to analyze the effectiveness of internal marketing and its relation to the outcomes: loyalty and performance. The research was conducted in a form of a questionnaire which enabled gathering information from volunteers and testing the stated hypotheses. The data was analyzed using correlation and multiple regression model. According to the results obtained, internal marketing practices are positively correlated with both loyalty and performance.